ZAKAT PAYMENT INCLUSION IN INDONESIA: A DESCRIPTIVE ANALYSIS OF ZAKAT MAAL COLLECTION, 2006–2015 - Canggih, Clarashinta; Fikriyah, Khusnul; Yasin, Ach. (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2017)
This paper aims to find out the amount of zakat fund collection, particularly zakat maal in Indonesia. Numbers of zakat fund collected is used to see zakat inclusion from the perspective of zakat payment of Indonesian. This paper uses descriptive quantitative through secondary data collection from several sources. The result shows that the realization of zakat fund collection in Indonesia increases during 2006-2015, so does the number of people who pay zakat. However, it can be seen that the zakat payment inclusion of Indonesian people is still low. The number of people who paid zakat is lower compare to the number of people who are obligated. It need further research to divulge the reason.